Mission impossible? The paradoxes of stretch goal setting. Issue 2 (April 2017) - Pina e Cunha, Miguel; Giustiniano, Luca; Rego, Arménio; Clegg, Stewart
Stretch goal setting is a process involving multiple and nested paradoxes. The paradoxical side of stretch is attractive because it holds great promise yet dangerous because it triggers processes that are hard to control. Paradoxes are not readily managed by assuming a linear relation between the here and now and the intended future perfect. Before adopting stretch goal setting, managers should thus be prepared for the tensions and contradictions created by nested or interwoven paradoxes. Achieving stretch goals can be as difficult for the managers seeking to direct the process as for designated delegates. While the increasing popularity of stretch goal setting is understandable, its unexpected consequences must be taken into account. The inadequate use of stretch goals can jeopardize the social sustainability of organizations as well as their societal support systems.